2018
DOI: 10.1002/14651858.cd011417.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 for maintaining ductal patency in neonates with ductal-dependent cardiac lesions

Abstract: There is insufficient evidence from randomized controlled trials to determine the safety and efficacy of PGE1 in neonates with ductal-dependent cardiac lesions. Evidence from observational trials have informed clinical practice on the use of PGE, which is now considered the standard of care for ductal-dependent cardiac lesions. It is unlikely that randomized controlled studies will be performed for this indication but comparative efficacy of newer formulations of PGE1, different doses of PGE1 and studies compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 53 publications
0
48
0
1
Order By: Relevance
“…7 They used oral prostaglandin E2 as an alternative medication for intravenous prostaglandin E. Although oral prostaglandin E2 was nearly effective, it required frequent administration and a substantial amount of the maintenance dose (27 μg/kg/hour) leading to several shortand long-term adverse effects. 5,7 Therefore, oral prostaglandin E2 might not have been suitable for clinical use and thus has not been widely used. Six years after the first report of oral prostaglandin E use, Saji et al reported the successful use of oral prostaglandin E1 in an infant with ductus-dependent pulmonary circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 They used oral prostaglandin E2 as an alternative medication for intravenous prostaglandin E. Although oral prostaglandin E2 was nearly effective, it required frequent administration and a substantial amount of the maintenance dose (27 μg/kg/hour) leading to several shortand long-term adverse effects. 5,7 Therefore, oral prostaglandin E2 might not have been suitable for clinical use and thus has not been widely used. Six years after the first report of oral prostaglandin E use, Saji et al reported the successful use of oral prostaglandin E1 in an infant with ductus-dependent pulmonary circulation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In patients with ductus-dependent circulation, free prostaglandin E1 (prostaglandin E1-CD) or lipid microspheres (lipo-prostaglandin E1) are indicated to maintain the ductus. 5 However, patients who are treated with prostaglandin E1 find it difficult to be discharged from the hospital because of the need for continuous intravenous administration of medications.…”
mentioning
confidence: 99%
“…On confirming our diagnosis, cessation of nitric oxide (a pulmonary vasodilator) was important as it would have resulted in increased pulmonary blood flow and further pulmonary venous obstruction. Instead, the use of alprostadil (prostin) ensured a vasodilatory effect and patency of the ductus arteriosus, promoting further right‐to‐left shunting of blood to maintain systemic cardiac output . Early recognition is crucial in ensuring appropriate management of infants with TAPVR.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the use of alprostadil (prostin) ensured a vasodilatory effect and patency of the ductus arteriosus, promoting further right-to-left shunting of blood to maintain systemic cardiac output. 8 Early recognition is crucial in ensuring appropriate management of infants with TAPVR. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They are coded by different genes, have different expression regulation mechanisms and signal transduction pathways. Activation of the EP3 receptor (so-called “inhibitory”) reduces the level of cyclic adenosine monophosphate (cAMP), whereas the EP2 and EP4 receptors (so-called “relaxing”) increase the level of cAMP [ 95 , 96 ]. PGE1 has strong vasodilatory, anti-inflammatory, anti-proliferative properties, is a strong platelet aggregation inhibitor, stimulates smooth muscles, reduces platelet hyperactivity and thromboxane A2 (TXA2) level, reduces free Ca 2+ levels in vascular smooth myocytes [ 97 , 98 ].…”
Section: Hormones With a Potential Nephroprotective Effectmentioning
confidence: 99%